2022
DOI: 10.3389/fneur.2022.915346
|View full text |Cite
|
Sign up to set email alerts
|

fMRI Findings in Cortical Brain Networks Interactions in Migraine Following Repetitive Transcranial Magnetic Stimulation

Abstract: BackgroundRepetitive transcranial magnetic stimulation (rTMS) is one of the high-potential non-pharmacological methods for migraine treatment. The purpose of this study is to define the neuroimaging markers associated with rTMS therapy in patients with migraine based on data from functional MRI (fMRI).Materials and MethodsA total of 19 patients with episodic migraine without aura underwent a 5-day course of rTMS of the fronto-temporo-parietal junction bilaterally, at 10 Hz frequency and 60% of motor threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(50 reference statements)
0
2
0
1
Order By: Relevance
“…The study conducted by Markin et al . [ 73 ] showed that the application of repetitive Transcranial Magnetic Stimulation (rTMS) for five days in 19 migraine patients was associated with FC changes within the default mode, salience and visual networks, which have been implicated in migraine pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Markin et al . [ 73 ] showed that the application of repetitive Transcranial Magnetic Stimulation (rTMS) for five days in 19 migraine patients was associated with FC changes within the default mode, salience and visual networks, which have been implicated in migraine pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
“…Another non-invasive neuromodulation method is the tDCS, which modulates the cortical activity by applying an excitatory or inhibitory electric current to the scalp [ 102 ]. Only two studies [ 73 , 74 ] have investigated functional and structural brain changes related to rTMS and tDCS treatments. The small sample size of these studies, the lack of a control group and the use of an uncorrected statistical threshold disallow solid conclusions regarding central modifications related to these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Методика фМРТ в состоянии покоя позволяет оценить базовую активность мозга в отсутствие определенных сенсорных или когнитивных стимулов. С помощью данной методики стало возможным изучение функциональной коннективности головного мозга, которая представляется в виде так называемых функциональных связей между различными участками головного мозга с формированием рабочих сетей покоя [8,9].…”
unclassified